Essential Work and Emergency Childcare: Identifying Gender Differences in COVID-19 Effects on Labour Demand and Supply - Jordy Meekes; Wolter Hassink; Guyonne Kalb (Institute of Labor Economics (IZA), 2020)
We examine whether the COVID-19 crisis affects women and men differently in terms of employment, working hours and hourly wages outcomes, and whether the effects are demand or supply driven. COVID-19 impacts are studied using administrative data on all Dutch employees up to 30 June 2020, focussing on the national lockdown and the emergency childcare for essential workers in the Netherlands. First, we find that the impact of COVID-19 is much larger for non-essential workers than for essential workers. Although, on average, women and men are equally affected, female non-essential workers are more affected than male non-essential workers. Second, partnered individuals with young children are equally affected by the crisis as others, irrespective of gender and spousal employment. Third, single-parent essential workers experience relatively large negative labour supply effects, suggesting emergency childcare was not sufficient for this group. However, overall, labour demand effects appear more important than labour supply effects.
Keywords: J13; J16; J20; J64; 330; COVID-19; gender; employment; hours worked; lockdown; essential workers